Antibacterial naphthoquinone derivatives targeting resistant strain Gram-negative bacteria in biofilms. (May 2018) - Novais, Juliana S.; Moreira, Caroline S.; Silva, Ana Carolina J.A.; Loureiro, Raquel S.; Sá Figueiredo, Agnes Marie; Ferreira, Vitor F.; Castro, Helena C.; da Rocha, David R.
Abstract: The aims of this study were the planning, synthesis and in vitro evaluation of 2-hydroxy-3-phenylsulfanylmethyl-[1, 4]-naphthoquinones against Gram-negative and Gram-positive strains, searching for potential lead compounds against bacterial biofilm formation. A series of 12 new analogs of 2-hydroxy-3-phenylsulfanylmethyl-[1, 4]-naphthoquinones were synthesized by adding a thiol and different substituents to a ο -quinone methide using microwave irradiation. The compounds were tested against Gram-positive ( Enterococcus faecalis ATCC 29212, Staphylococcus aureus ATCC 25923, S. simulans ATCC 27851, S. epidermidis ATCC 12228 and a hospital Methicillin-resistant S. aureus (MRSA) strain), as well as Gram-negative ( Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, P. aeruginosa ATCC 15442, Proteus mirabilis ATCC 15290, Serratia marcescens ATCC 14756, Klebsiella pneumoniae ATCC 4352 and Enterobacter cloacae ATCC 23355) strains, using the disk diffusion method. Ten compounds showed activity mainly against Gram-negative strains with a minimal inhibitory concentration (MIC = 4–64 μg/mL) within the Clinical and Laboratory Standards Institute (CLSI) levels. The biofilm inhibition data showed compounds, 9e, 9f, 9j and9k, are anti-biofilm molecules when used in sub-MIC concentrations against P. aeruginosa ATCC 15442 strain. Compound (9j ) inhibited biofilm formation up to 63.4% with a better profile than ciprofloxacin, which is not able to prevent biofilm formation effectively. The reduction of P. aeruginosa ATCC 15442 mature biofilms was also observed for9e and9k . The structure modification applied in the series resulted in 12 new naphthoquinones with antimicrobial activity against Gram-negative bacteria strains ( E. coli ATCC 25922, P. aeruginosa ATCC 27853 and ATCC 15442). Four compounds decreased P. aeruginosa biofilm formation effectively. Highlights: Synthesis of 12 new analogs of 2-hydroxy-3-phenylsulfanylmethyl-[1, 4]-naphthoquinones. Ten compounds showed activity mainly against Gram-negative strains. Two compounds promoted the reduction of P. aeruginosa ATCC 15442 mature biofilms. One compound inhibited biofilm formation up to 63.4% with a better profile than ciprofloxacin.